Vision, narrative, and wisdom in the Aramaic texts from Qumran: essays from the Copenhagen Symposium, 14-15 August, 2017 - Bundvad, Mette; Siegismund, Kasper; Bach, Melissa Sayyad; Holst, Søren; Høgenhaven, Jesper (Studies on the texts of the desert of Judah, 2019)
This volume is a collection of scholarly articles on the Aramaic Dead Sea scrolls, some of the oldest and most fascinating literary compositions among the ancient Jewish manuscripts found in the Qumran caves. Readership: Anyone interested in the Bible, ancient Judaism, the Dead Sea Scrolls, biblical interpretation, and the history of religion